Application of oxidative enzymes in membrane systems for the bioremediation of triazines in wastewater - Lesaoana, Mahadi (University of the Witwatersrand, Johannesburg, 2024)
The prevalence of herbicidal pollutants present in various environmental matrices have become a global concern. The discharge and accumulation of s-triazine agrochemicals in effluents remains a major challenge, threatening the quality of freshwater resources. These are newly identified recalcitrant contaminants of concern (CECs) with complex structures, and inadvertent exposure poses deleterious ecological risks and human health-related adverse effects. Unfortunately, they have shown resistance to conventional treatment strategies, hence their persistence in wastewater treatment plant (WWTP) effluents and water bodies. Therefore, there is an urgent need for the exploration of alternative technologies for the effective eradication of such contaminants from water samples. The bioconversion of such micropollutants using oxidative enzymes like laccase is a promising research avenue, providing a sustainable, economically and ecologically benign strategy. The current research examined the potential of a hybrid biocatalytic membrane system to degrade common s-triazine agrochemical herbicides in aqueous solutions. Specifically, the use of Novoprime base 268 laccase coupled with hollow fibre polyethersulfone (PES) membranes was investigated for the bioremediation of atrazine (ATZ), ametryn (AMT), simazine (SMZ) , prometon (PMT) and terbuthylazine (TERB) in wastewater. In batch-mode reactions, major operating parameters (i.e. pH and temperature profiles, enzyme dosage and contact time) were varied for the laccase-assisted catalysis of s-triazine compounds. Optimised conditions provided highest removal efficiencies (> 88.9%) at pH 5.0, combined with a temperature of 25°C and 1.0 mg L-1 solution concentration after 24h reaction time. Through the addition of redox mediators viz. 2,2-azino-bis-3-ethylbenzothiazoline-6-sulphonic acid (ABTS), violuric acid (VA), vanillin (VA), syringaldehyde (SRA) and acetosyringone (ASR) recalcitrant triazine degradation was enhanced by 10 to 20 % at 1.50 mm. Subsequently, the performance of a standalone continuous flow-mode membrane system was evaluated firstly, using a bed adsorption column only operated under various conditions. The efficiencies were compared to batch-mode enzymatic experiments. The adsorption of triazines by PES was only weakly influenced by pH, and the optimum removal was attained at pH 5.0 (5.0 mg L-1), 2.35 g bed mass (14.0 cm height) and 24h column operation time. The overall removal percentages were 72.6%, 75.2%, 71.4%, 67.4%, and 68.2% for ATZ, AMT, SMZ, PMT and TERB, respectively. Although the results indicated satisfactory performances by both systems, their performance is limited when used as separate units (continuous membrane vs laccase reactor). A biocatalytic membrane system was achieved by integrating laccase into the dynamic packed-bed membrane column. Relevant process control design parameters of the fixed-bed biocatalytic column were carefully evaluated and recorded an optimum of 93.2 % removal efficiency as observed at a feed flow rate 2.0 mL min-1, at a bed height of 14.0 cm using an atrazine influent concentration of 5.0 mg L-1. Equilibrium dynamics of the breakthrough modelling were best fitted by Thomas model. Results attained demonstrated selectivity for triazines in matrix-matched real river water samples with remarkable recyclability after six successive operational cycles. This reflects the potential workability of the integrated system for extended enzymatic reactions evaluated under robust experimental conditions. As a benchmarking exercise, cost-analysis studies showed comparable projected scalability of our configuration at 1200 m3/d capacity at an estimated total cost of R7.036 mil.
A thesis submitted in Fulfilment of the Requirements for the Degree of Doctor of Philosophy, to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2024.
Keywords: Polyethersulfone; Laccase; Bioremediation; Enzyme; Biocatalysis; Wastewater; s-Triazines; Herbicides; UCTD; SDG-13: Climate action; SDG-6: Clean water and sanitation